Undergraduate Research - Madeeha Nazar, Madeeha Nazar (Students’ Supplement of Journal of Rawalpindi Medical College, 2022)
For people in medical field research is a continuous non ending process. Conducting research is an important component of post graduate training throughout the World. Recently more and more emphasis is being given to start research at undergraduate level.1 This trend is facing difficulty in implementation due to a number of factors that relate to undergraduate researchers, their research supervisors, and publishers.2 In this context most important is undergraduates lack of knowledge and training on how to conduct a research and bring it to black and white form. They also need guidance on selection of a suitable topic that is doable with their college routine and busy study schedule. In order to write the topic of research, researchers must study and understand it in detail. This requires motivation and some incentive as well. Often there is difficulty in literature review due to limitation of access to journals that require payment. Sometimes the topic selected requires financial support that is not easily available. Data collection also requires hard work and planning. Many of the undergraduate researchers are not skilled at performing statistical analysis. Sometimes the supervisors allot them topics that are either too difficult or are of not much interest to them .This results in lack of motivation to do research then and in future as well.